Efficacy of Erbium-Doped Yttrium Aluminium Garnet 2, 940 and 1, 064 nm Laser Treatment for Facial Rejuvenation—A Randomized Controlled Split-Face Clinical Trial. Issue 11 (November 2021) - Song, Wenting; Tian, Yangzi; Tan, Wenbin; Wang, Gang; Gao, Lin
Abstract : BACKGROUND: The 2, 940 nm erbium-doped yttrium aluminium garnet and 1, 064 nm neodymium-doped yttrium aluminium garnet lasers have been widely applied in facial rejuvenation, but no randomized trials exist to evaluate the efficacy of the combination treatment. OBJECTIVE: The efficacy of the combined treatment for facial rejuvenation. MATERIALS AND METHODS: A total of 20 subjects with facial aging were enrolled and randomly assigned into 2 groups: one side of the face was treated with a 2, 940 nm or 1, 064 nm laser alone and the other side was treated with the combined lasers. The patients were treated by 3 sessions with 1-month intervals. The efficacies were quantitatively accessed by digitalized high-resolution photographs. RESULTS: The 1, 064 nm laser alone showed significant improvements on indexes of skin texture, spore, brown spots, elasticity, and melanin as compared with the baseline ( p < .05). The 2, 940 nm laser alone showed significant improvements on indexes of wrinkle, texture, pore, and elasticity ( p < .05). The combined treatments showed significant improvements on the abovementioned indexes as compared with either a 1, 064 nm or 2, 940 nm laser treatment ( p < .05). CONCLUSION: A combination of 1, 064 nm and 2, 940 nm laser treatment renders significantly better efficacies for facial rejuvenation as compared with a 2, 940 nm or 1, 064 nm laser alone.